Desa Digital dan Tingkat Literasi Keuangan Aparatur Desa: Studi Kasus Kabupaten Aceh Tamiang - Fitriansyah, Fitriansyah; Nuryakin, Chaikal (Jurnal Ekonomi dan Pembangunan Indonesia, 2021)
Since 2014, to reach the poor for increasing financial inclusion, the government of Indonesia has been digitizing social benefits. Recently, local government has also been pushed to build a “Digital Village.” We argue that for such a program to succeed, a good level of financial and digital literacy of the village officials is necessary. We surveyed the village officials in 60 out of 215 Aceh Tamiang to examine their financial, digital, and DFS literacy. We find that the literacy of the village officials, on average, is low. The factors contributing to low financial literacy are age, level of education, and accessibility to financial and digital services.